The Prevalence, Intensity and Extent of Oral Impacts on Daily Performances among the Patients Wearing Orthodontic Appliances (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2016)
Objectives: To evaluate the frequency, severity and extent of Oral Impact on Daily Performances (OIDP) in the patients wearing orthodontic appliances in relation to type of orthodontic appliances and sex of patients.Materials and method: This was a descriptive cross sectional study with 287 participants by convenient sampling aged 10-25 years, undergoing orthodontic treatment at the department of Orthodontics & Dentofacial Orthopedics of Dhaka Dental College & Hospital. Face-to-face structured interviews and clinical examination were done to collect information about impacts on quality of life related to wearing orthodontic appliances, using the OIDP.Results: Two hundred and eighty seven patients (31% male and 69% female) undergoing orthodontic treatment participated in the study. The prevalence of condition-specific impacts related to wearing orthodontic appliances was 30.7%. Among adolescents with impacts related to wearing orthodontic appliances, 16.8% reported impacts of severe intensity and 90.5% reported impacts on only one daily performance, commonly eating or speaking or cleaning mouth. The prevalence and the extent, but not the intensity of condition-specific impacts differed by type of orthodontic appliance (P =.023* and .0426* respectively).Conclusion: Less than one third participants undergoing orthodontic treatment reported side effects, specific impacts on daily living, related to wearing orthodontic appliances. Such impacts were higher among patients wearing fixed type of orthodontic appliances than removable type. This information could help to inform patients about the frequency, intensity & extent of sociodental impacts during the course of their treatment and thereby increase the treatment compliance.Ban J Orthod & Dentofac Orthop, April 2016; Vol-6 (1-2), P.6-12